Sistem Alat Ukur Kekeruhan Berbasis Mikrokontroler ATMega16A-PU - Muhammad Mispu Ariadi; Iwan Sugriwan; Arfan Eko Fahrudin (Jurnal Fisika FLUX, 2019)
The fabrication of the ATMega16A-PU microcontroller-based the system turbidity sensor consists of sensor module Turbidity SKU:SEN0189 including with the signal conditioning, power supply unit, the ATMega16A-PU microcontroller  module, LCD 16 x 2 character, and personal computer (PC). The measuring system is used to measure the quality of water on theriverMartapura South Kalimantan, Indonesia. The physical parameters that measured is the of water. The measuring of turbidity detected by the sensor through the light that traverse the suspended particles in water. The output signal from the sensor in from of the voltage signal is connectedwith ATMega16A-PU microcontroller viaport A0. The voltage signal output is inversely proportional to the turbidity. Theequation of sensor characteristic is obtained by comparing the measuring device with HACH DR 890 Colorimeter turbid meter gauge. The characteristic equation obtained is counted into five equations to get a small error value, where v1 = -0.0036k1 + 4.0834, v2 = -0.0024k2 + 3.9351, v3 = -0.003k3 + 4.1777, v4 = -0.0033k4 + 4.3355, v5 = -0.0034k5 + 4.4315, the five equations have different measurement ranges. The result of data measurement are displayed on the LCD 16 x 2 character and the personal computer (PC) with the Delphi.7 interface program. The advantages of personal computer (PC) interface are the data measurement result could monitor and stroge in excel and database format. The results of the measuring instrument show a difference of 1 NTU to 15 NTU with the largest deviation is ± 28.7 and a standard deviation of ± 4.57 in the range of 31 NTU to 510 NTU